What does a corpus of text messages tell us about syntactic variation? The case of yes/no questions in European French - Guryev, Alexander (My University, 2014)
The aim of the present contribution is to show that a traditional explanation of the variation in French yes/no questions, which is widely used in L2 French classroom learning, and according to which French interrogatives express different socio-stylistic values, needs to be challenged. The main result of this research, based on a study of 1’659 yes/no questions (YNQ) extracted from 4’624 text messages taken from the Swiss SMS Corpus (http://www.sms4science.uzh.ch), suggests that one should consider communicative and linguistic constraints to account for the variety of interrogative forms in French.
, The NWAV 43, University of Illinois at Urbana-Champaign and University of Illinois Chicago, October 23-26, 2014., Chicago
Keywords: Syntactic variation; French interrogatives; SMS communication